Econometric Models in Romanian Tourism under the Impact of Sustainable Development - Delia Popescu; Andreea Saseanu; Daniel Bulin; Grazia Calabro (Amfiteatru Economic Journal, 2014)
After the year 1989 Romanian tourism has grown chaotic and failed to have any link to the concept and sustainable development principles. Sustainability, in general, and the tourism sustainability, especially, combine different aspects – economic, social, environmental etc. in a harmonious way. In the paper the authors have proposed to test multiple linear regression models, in order to, finally demonstrate the impact of sustainable development on tourism activity. Following analyses have established links between nature, size of the tourism, economic, social and ecological indicators, thus demonstrating the impact of sustainable development on tourism also. The authors propose two original econometric models of dependence between the index of net using the tourist accommodation capacity in operation and indicators expressing the quality of life and sustainable development.
Keywords: Q01; L83; C32; 330; sustainable development; quality of life; tourism indicators; econometric